Testing for a significant change in the Egyptian economy under the economic reform programme era - Mohammed Omran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Late 1990, Egypt witnessed major and radical changes in all areas of its national life— political, legal, economic and social—as a reflection of implementing an economic reform programme in order to achieve progress in its economic indicators. This paper aims to examine the extent to which Egypt has succeeded in implementing its economic reform programme, and how this affected key aspects of the whole economy. For this purpose, logistic regression is made to determine whether the Egyptian economy has changed after 1991, the year of introduction of the economic reform programme. Particular attention is paid to several economic variables, mainly, interest rates, real interest rates, rate of inflation, exchange rate stability, real GDP growth rate, per capita income, and the budget deficit. The logistic regression results indicate that there is strong evidence that after 1991, with the exception of real GDP growth rate, there was a structural change in economic indicators.
Keywords: E6; O1; P22; 330; public finance; development; prices; Entwicklung; Wirtschaftsreform; Ägypten